MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP MELALUI MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE (SSCS) - Heru Sujiarto; Tita Sukmiati (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
This research is motivated by the low value of daily test of students on the subject of Equation of Straight Line which is more than for half does not reach the minimum completeness criteria (KKM) of the set standard is 70.00. The low learning outcomes of students indicate that the learning process has not run optimally. Therefore, in need of learning alternatives that support students to think creatively, to improve the KKM, one of them using Search model, solve, create, and share (SSCS). This study aims to determine the improvement of students' creative thinking ability by using SSCS learning model on straight-line equation. This research is a Classroom Action Research (PTK). Carried out in three cycles. Cycle 1 consists of two meetings, cycle 2 and cycle 3 each consisting of one meeting. Instruments used to collect data consist of creative thinking ability test, instructional learning observation sheet with SSCS model, and student response questionnaire to learning with SSCS model. The results obtained from this research are 1) students' creative thinking ability increases after learning by using SSCS learning model; 2). Student learning completeness on the subject The equation of Straight line increases after learning with SSCS learning model; 3) students respond positively to mathematics learning using SSCS method